1996
DOI: 10.1021/om950835w
|View full text |Cite
|
Sign up to set email alerts
|

Self-Activation of a Cluster-Bound Alkyne toward Carbon−Carbon Bond Forming Reactions

Abstract: The methanol-catalyzed elimination of Cl- from the “activated” anionic species [PPN][Ru3(μ-Cl)(μ-PhCCPh)(CO)9] (1) in the presence of bis(diphenylphosphino)methane (dppm) constitutes a rational high-yield route (>90%) to either the unique unsaturated 46-e (alkyne)triruthenium cluster, Ru3(μ-PhCCPh)(CO)7(dppm) (2), or its 48-e CO adduct, Ru3(μ-PhCCPh)(CO)8(dppm) (3). Whereas the CO-induced conversion of 2 into 3 is complete within few seconds at 25 °C under 1 atm of CO, the reverse transformation takes 1 h at 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 86 publications
1
23
0
Order By: Relevance
“…This suggests that these compounds are isostructural with the symmetrical derivative 3 11 whose dppm phosphorus atoms are equivalent and whose structure is proposed here to contain a CO and a dppm ligands bridging the same edge which is also parallel to the µ 3 -η 2 -alkyne 14 (see Scheme), although the X-ray molecular structure of the closely related cluster [Ru 3 (µ 3 -η 2 -PhC 2 CCPh)(µ-dppm)(µ-CO)(CO) 7 ] has been reported to be slightly different 15 with the bridging CO bonded to a different metal edge. Contrary to the analogous clusters 3, 4 and 5 and other clusters of the series containing a dppm instead of two CO ligands, 11,16 it was impossible to decarbonylate 2 to yield the unsaturated cluster [Ru 3 (µ 3 -η 2 -FcCCC 6 H 4 -4-NO 2 )(µ-dppm)(CO) 7 ] with the alkyne bonded in the perpendicular mode. Compound 2 was stable when heated in toluene, at 80 °C, for 4 h, but upon increasing the temperature it underwent decomposition.…”
Section: Resultsmentioning
confidence: 95%
“…This suggests that these compounds are isostructural with the symmetrical derivative 3 11 whose dppm phosphorus atoms are equivalent and whose structure is proposed here to contain a CO and a dppm ligands bridging the same edge which is also parallel to the µ 3 -η 2 -alkyne 14 (see Scheme), although the X-ray molecular structure of the closely related cluster [Ru 3 (µ 3 -η 2 -PhC 2 CCPh)(µ-dppm)(µ-CO)(CO) 7 ] has been reported to be slightly different 15 with the bridging CO bonded to a different metal edge. Contrary to the analogous clusters 3, 4 and 5 and other clusters of the series containing a dppm instead of two CO ligands, 11,16 it was impossible to decarbonylate 2 to yield the unsaturated cluster [Ru 3 (µ 3 -η 2 -FcCCC 6 H 4 -4-NO 2 )(µ-dppm)(CO) 7 ] with the alkyne bonded in the perpendicular mode. Compound 2 was stable when heated in toluene, at 80 °C, for 4 h, but upon increasing the temperature it underwent decomposition.…”
Section: Resultsmentioning
confidence: 95%
“…f Fe 3 (CO) 9 (C 2 Et 2 ) [11]. g Ru 3 (CO) 7 (dppm)(C 2 Ph 2 ) [14]. h Fe 3 (CO) 9 [SiFe(CO) 2 Cp] 2 [20].…”
Section: Bipyramidal Triangular 6-sep M 3 (Co) 9 E 2 Clustersmentioning
confidence: 99%
“…Hence, if a biphasic hexane/ methanol solvent mixture is used, the neutral complex Ru 3 (µ-RCCR)(µ-CO)(CO) 9 transfers itself to the hexane HCϭCPhϪC(O)ϪPhCϭCPh appeared as the result of an intramolecular alkyne/CO/alkyne coupling. [41] Bearing in phase, from which it can be recovered pure without chromatographic workup.…”
Section: Chemistry Of "Anion-promoted" Rutheniummentioning
confidence: 99%
“…This is illustrated in Scheme 7. [41] We first made the encouraging observation that the cluster-I.2.3 Activation of Olefins bound alkyne ligand in the triruthenium complex Ru 3 (µ-PhCCPh)(µ-dppm)(CO) 7 could be readily engaged in CϪC In 1986, Gladfelter and co-workers reported that olefins can be readily hydrogenated at ambient temperature in the bond formation with an incoming phenylacetylene molecule within minutes at 0°C, giving the coordinatively unsatu-presence of the isocyanatotriruthenium cluster complex [Ru 3 (NCO)(CO) 10 ] Ϫ , [43] another member of the growing rated "fly-over"-type complex Ru 3 [µ-PhCCPhϪC(O)ϪPh-CCH](µ-dppm)(CO) 6 where the dialkenyl ketone fragment family of "anion-promoted" triruthenium clusters.…”
Section: Facile Dehydration Of a Cluster-bound Alkynolmentioning
confidence: 99%